القوة الناعمة في العلاقات الدولية دراسة حالة تركيا 2002-2017 - نفطية, محمد (جامعة الوادي University of Eloued, 2017)
لطالما أثار مفهوم القوة في العلاقات الدولية جدلا واسعا منذ القديم، يوم أن كان مفهوم القوة مقتصراً على القوة العسكرية، والذي اصطلح عليه في التنظير المعاصر بالقوة الصلبة، في مقابل أنواع أخرى من القوة اصطلح عليها بالقوة الناعمة. وتعتبر دولة تركيا خاصة من تولي السلطة فيها حرب العدالة والتنمية أواخر سنة 2002 إلى يومنا هذا من الدول الرائدة في استعمال القوة الناعمة في سياستها الخارجية. وقد اعتمدت تركيا القوة الناعمة في مختلف أنواعها ومستوياتها من الثقافة الإعلامية إلى السياحية والاقتصادية وكذلك الدبلوماسية والعلاقات الخارجية وغيرها. كما خلصنا في هذه الدراسة إلى أن القوة الناعمة وحدها لا تكفي لزيادة تأثير ونفوذ الدولة على الساحة الدولية، بل لا بد من تعضيدها بالقوة الصلبة وهو ما اصطلح على تسميته بالقوة الذكية. ويبقى المجال مفتوحا للبحث حول حدود كل من القوتين الصلبة والناعمة، سياسة الدولة الخارجية ومختلف العوامل المؤثرة، توسيع مساحة هذه أو تلك، خاصة في ظل تعقد العلاقات الدولية، وشدة المنافسة والصراع فيها، في مقابل سعي عدد من الدول وهو في تزايد مستمر إلى تغليب جانب التعاون الدولي على الصراع، بتشجيه من كثير من المنظمات الدولية الإقليمية The concept of power in international relations has long been controversial since the concept of force was limited to military force, which was used in contemporary theory of hard power, as opposed to other types of force that were called soft power. The State of Turkey in particular, from which the Justice and Development War took over in late 2002 to this day, is one of the leading countries in the use of soft power in its foreign policy. Turkey has adopted soft power of various types and levels of media culture to tourism and economic as well as diplomacy, foreign relations and others. In this study, we conclude that soft power alone is not sufficient to increase the influence and influence of the state on the international scene, but must be supported by solid power, which is called smart power. It remains open to research on the limits of both solid and soft forces, the foreign policy of the State and various factors affecting the expansion of the space of one or the other, especially in light of the complexity of international relations and the intensity of competition and conflict in return for the pursuit of a number of countries International cooperation in conflict, with the provocation of many regional international organizations.
نظم سياسية مقارنة وحكم راش
Keywords: القوة الناعمة، العلاقات الدولية، تركيا، نظرية العمق الاستراتيجي، القوة الذكية; Soft power, international relations, Turkey, strategic depth theory, smart power.